The Effectiveness of Trauma-Informed Care in Midwifery Services on the Psychological Recovery of Mothers with a History of Gender-Based Violence in Medan - Nurhaida Br. Kaban; Anita Yasmin (ALINEA: Health Science & Medical International Journal, 2025)
Background: Gender-based violence (GBV) remains a major public health issue that negatively affects women’s psychological well-being and reproductive health. Trauma-informed care (TIC) is an approach to health services that recognizes the long-term effects of trauma and incorporates this understanding into all aspects of patient care. This study aimed to evaluate the effectiveness of TIC implementation in midwifery services on the psychological recovery of pregnant and postpartum women with a history of GBV in Medan City. Methods: This study applied a quasi-experimental pre-test and post-test control group design involving 86 pregnant and postpartum women identified through GBV screening at six primary health centers in Medan. Participants were divided into a TIC intervention group (n=43) and a control group (n=43). Psychological outcomes assessed included post-traumatic stress disorder symptoms using the PCL-5, depression with the EPDS, anxiety with the GAD-7, self-efficacy with the GSE, and mother–infant bonding using the PBQ. Data collection was conducted at baseline, week 8, and week 16. Statistical analysis employed repeated measures ANOVA and multiple linear regression.Results: Women receiving TIC showed significantly better psychological outcomes at week 16 compared with the control group. PTSD, depression, and anxiety scores decreased significantly, while self-efficacy and mother–infant bonding improved markedly (p<0.001). TIC also emerged as an independent predictor of psychological recovery after adjustment for confounding variables (β=-0.48; p<0.001). Conclusion: Trauma-informed care in midwifery services effectively enhances psychological recovery among women with GBV histories and should be integrated into maternal healthcare standards for vulnerable populations in Indonesia.